Catatonia secondary to synthetic cannabinoid use in two patients with no previous psychosis. (January 2016) - Khan, Madiha; Pace, Lauren; Truong, Anh; Gordon, Mollie; Moukaddam, Nidal
Abstract : Background and Objectives: Synthetic cannabinoids (SC) have become widely abused as recreational drugs, and are now known to carry risk of severe mental and physical health effects. Catatonia, spanning the gamut from motor retardation to agitation, can constitute a psychiatric emergency for which benzodiazepines are the mainstay of treatment. The purpose of this paper is to report on an unusual occurrence of catatonia in the context of synthetic cannabinoid use, and a discussion of treatment options that have been helpful as adjuncts to benzodiazepines. Methods: We present two cases of catatonia occurring in context of SC use. The first patient was using SC quasi‐daily for 18 months. The second patient used a large quantity over a two‐week period. Both patients were admitted to our emergency center with catatonia and no overt psychosis or mood symptoms. Results: The absence of pre‐existing mood or psychotic disorder and the severity of catatonic symptoms separates these cases from other cases reported in the literature. Additionally, pharmacological management targeting gamma‐aminobutyric acid (GABA) and serotonin neurotransmitter systems were used, specifically aripiprazole and valproic acid, supplementing benzodiazepine administration; these were needed for optimal symptom control. Conclusions and Scientific Significance: The above‐reported cases are highly significant because of the severity of catatonic symptoms requiring inpatient hospitalization, the potential for rapid and severe decompensation with catatonia, and the atypical/unexpected development of catatonia with SC use. (Am J Addict 2016;25:25–27)